Intrahepatic infiltration of activated CD8+ T cells and mononuclear phagocyte is associated with idiosyncratic drug-induced liver injury - Yang, Hyun; Han, Ji Won; Lee, Jae Jun; Lee, Ahlim; Cho, Sung Woo; Rho, Pu Reun; Kang, Min-Woo; Jang, Jeong Won; Jung, Eun Sun; Choi, Jong Young; Sung, Pil Soo; Bae, Si Hyun (Frontiers in Immunology, 2023)
Background Idiosyncratic drug-induced liver injury (DILI) is caused by the interplay among drugs, their metabolites, and the host immune response. The characterization of infiltrated immune cells in the liver may improve the understanding of the pathogenesis of idiosyncratic DILI. This study investigated the phenotypes and clinical implications of liver-infiltrating immune cells in idiosyncratic DILI. Methods From January 2017 to June 2021, 53 patients with idiosyncratic DILI who underwent liver biopsy were prospectively enrolled in this study. Immunohistochemical staining and flow cytometry analyses were performed on the biopsy specimens. Serum levels of CXC chemokine ligand 10 (CXCL10) and soluble CD163 were measured. A multivariate cox proportional hazards model was used to evaluate predictors of DILI resolution within 30 days. Results The numbers of intrahepatic T cells and mononuclear phagocytes were positively correlated with serum levels of total bilirubin, alanine aminotransferase (ALT), and the model of end-stage liver disease score. The frequency of activated CD8+ T cells among liver-infiltrating CD8+ T cells in DILI livers was higher than that in healthy livers. Notably, the percentages of activated intrahepatic CD8+ T cells and mononuclear phagocytes in DILI livers showed a positive correlation with ALT. Additionally, serum CXCL10 level was positively correlated with intrahepatic T cell infiltration and ALT, and soluble CD163 level was positively correlated with intrahepatic mononuclear phagocyte infiltration and ALT. Thirty-six patients (70.6%) were treated with steroids. In multivariate analysis, total bilirubin and steroid use independently influenced DILI resolution within 30 days. Conclusions Activated CD8+ T cells and mononuclear phagocyte are associated with liver injury caused by drugs. Therefore, we suggest that steroids are a potential treatment option for idiosyncratic DILI.